The Equity Premium Puzzle in the Czech Republic - Skála, Jaromír; Potužák, Pavel; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2023)
This thesis examines the equity premium puzzle in the Czech Republic using a consumption-based asset pricing model with time-separable preferences. The equity premium puzzle, which states a disproportionate differential between returns on risky and risk-free assets, cannot be adequately explained by the traditional coefficient of risk aversion, as it should be significantly lower based on microeconomic evidence. This study begins with a comprehensive literature review of the theoretical background of the equity premium puzzle and various attempts to solve it. This thesis utilizes data spanning the period 1997 to the first half of 2023. To ensure the reliability of the outcomes, multiple measures of the risk-free rate and multiple measures of return on equity were incorporated into the analysis. This study is unique in that it utilizes the geometrical average as an estimator, which enhances the reliability of the results by accounting for the unsteady nature of Czech data. Although the value of risk aversion resulting from this thesis is considerably lower than that reported in Mehra and Prescott’s (1985) seminal study, the subjective discount factor does not fall within its admissible interval. Additionally, data from the Czech Republic suggest a lack of stability in the short term.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses